IN VITRO STIMULATION OF ANTITUMOR CYTOTOXIC ACTIVITY OF MONONUCLEAR CELLS FROM COLORECTAL CANCER PATIENTS - V. V. Kurilin; Yu. N. Khantakova; I. A. Obleukhova; Yu. A. Shevchenko; E. V. Kulikova; V. K. Yakushenko; A. V. Sokolov; S. V. Sennikov (Медицинская иммунология)
Abstract. In present study, we investigated the in vitro ability of autologous dendritic cells loaded with tumor lysate antigens to stimulate cytotoxic and secretory activity of effector cells from patients with colorectal cancer. To this purpose, we generated antigen-primed dendritic cells (DS) derived from adherent fraction of peripheral blood mononuclear cells (PBMSc) obtained from patients with colorectal cancer. The DCs were then cocultured with non-adherent mononuclear cells, either in presence of IL-12 and IL-18, or without cytokines. The modulation efficiency was assessed as cytotoxic activity of mononuclear cells towards autologous tumor cells, production of IFNγ, IL-2, IL-4 and the number of perforin-, granzyme B-containing cells. We have demonstrated the ability of dendritic cells to stimulate the in vitro antitumor cytotoxic and secretory activity of effector cells in culture. A combination of dendritic cells with IL-12 and IL-18 is shown to enhance their effects in the mononuclear cells culture, as evidenced by increased percentage of dead autologous tumor cells, higher numbers of perforin(+), granzyme B(+) lymphocytes, and increased production of IFNγ, IL-2 increased.